The capability of places: methods for modelling community response to intrusion and change - Wallman, Sandra; Bond, Virginia (Virginia Anne); Montouri, Maria Alessia; Vidali, Mai.; Lo Conte, Rossella (London: Pluto Press; New York: Palgrave Macmillan [exclusive U.S.A. distributor], 2011)
"How can we assess the ability of a place to respond to challenges like migration, recession and disease? Places which seem similar can respond very differently, and with varying degrees of success, to external threats and to the interventions designed to manage them. In this ... work, drawing on decades of research, Sandra Wallman explores how we can measure and compare the resilience of communities, looking in detail at neighbourhoods in London, Rome and Zambia. Each locale is examined as a system which is more or less open or closed; open systems tend to be more resilient when faced with external challenges. As well as being a fascinating study in its own right, the book includes detailed accounts of the research methods used, as well as a user-friendly typology for classifying local systems, making it an invaluable tool for students, researchers and policy-makers."--Publisher's website.
Themes and a model -- London, ethnicity or localism? -- Rome, migrants and migration -- Zambia, terrains and tuberculosis -- Three sets of methods, one methodology -- Towards typology.
Includes bibliographical references (p. 165-167) and index.
Keywords: Ethnology -- Research; Communities -- Research; Community development